Development of sense organs and mouth and feeding of reared marble goby Oxyeleotris marmoratus larvae - Senoo, Shigeharu; Ang, Kok Jee; Kawamura, Gunzo (1994)
To obtain the fundamental information required to establish an artificial seed production technique for the marble goby Oxyeleotris marmoratus, the development of sense organs and mouth and the feeding of the larvae were observed. The larvae exhibited a S-posture and horizontal swimming at 2 days after fertilization (d AF) and commenced feeding on phytoplankton (species unknown) at 3 d AF when the eyes, the otic vesicle with ciliated epithelium, the free neuromasts on the head and the trunk, and the ciliated olfactory epithelium were functional. The first taste buds appeared in the oral cavity at 6 d AF after the onset of feeding on Brachinous spp. The larvae commenced feeding on Cyclops sp. at Id AF, Moina sp. at 10d AF, and Anemia salina nauplii at 15 d AF. This change of feeding might be due to the development of the mouth and mobility of larvae rather than the development of sense organs. At 20 d AF, the larvae developed free neuromasts on the caudal fin. Twin cones and rods appeared in the ratinae at 30 d AF when the larvae changed in phototaxis from positive to negative. The larvae became benthic in habit at 35 d AF. © 1994, The Japanese Society of Fisheries Science. All rights reserved.